Various protein-based coating towards postharvest quality of papaya (Carica papaya) / Aiza Izyan Mudzafar, Khawarizmi Mohd Aziz and Muhammad Nuruddin Mohd Nor - Mudzafar, Aiza Izyan; Mohd Aziz, Khawarizmi; Mohd Nor, Muhammad Nuruddin (Faculty of Plantation and Agrotechnology, 2023)
Postharvest losses are a serious problem because produce degrade quickly when handled, shipped, and stored. Edible coatings are applied to fresh produce to maintain their quality and extend shelf life. Papaya is a significant tropical crop that is consumed globally. However, papaya's natural shelf life is limited due to its rapid ripening and susceptibility to fungal infections, necessitating postharvest treatment. This research investigated how different edible protein coatings can extend the shelf life of papaya. For this experiment, four treatments were used: control, whey, sesame, and soy, as well as 2% Tween as a plasticizer, with four replications for each treatment. The study also looked at the impact of various edible protein coatings on papaya sugar content, physiological water loss, skin color changes, and the severity of disease incidence. Soluble solid concentration results show a significant difference for treatment 1 with a value of 7.50 brix. The skin color reveals a significant difference, with treatment 1 scoring an 8.00. Disease severity score from treatment 1 differs significantly as well, with a score of 9.00. Treatment 4 has the highest mean of 26.98, and there is no significant in physiological water loss. Finally, the results of treatment 1 showed that papaya cannot be stored for more than 7 days after losing some of its shelf life. Treatment 3, which is coated with sesame protein, is the most effective method for extending the shelf life of papaya.